CHALLENGES IN CAREER DEVELOPMENT OF THE FUNCTIONAL POSITION OF SUPERVISORY OF REGIONAL GOVERNMENT AFFAIRS (PPUPD) IN THE INSPECTORATE OF THE PROVINCE OF THE SPECIAL CAPITAL OF JAKARTA - Mutiah Mutiah; Lina Miftahul Jannah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Career development in a government agency is very important for the progress and success of the organization in achieving the planned goals. The formulation of the problem is how to challenge the career development of PPUPD functional positions at the DKI Jakarta Provincial Inspectorate. The purpose of this study was to determine the implementation of career development at the Inspectorate of DKI Jakarta Province and the challenges in career development of PPUPD. The research method uses a qualitative descriptive method. Data collection was obtained through informant interviews and document studies. The results of the study concluded that the implementation of career development in PPUPD functional positions was influenced by several factors. Factors that support career development are the implementation of training for all employees and the availability of a budget. While the inhibiting factors are fair treatment in a career, concern for direct superiors, information on promotion opportunities, and interest in being promoted.